Simple Linear Regression Analysis of Temperature Trends using R Language: Case Study of Palembang City 1991-2020 - Alfikro, Ihsan; Harisdianto, Harisdianto; Adnan, Assaidah; Affandi, Azhar Kholiq; Setiabudidaya, Dedi (Jurnal Penelitian Sains, 2024)
Global warming is the most world priority of environment issues, which is indicate continously increment of  global mean temperature of Earth. Various research shown detrimental impact of Earth environment, due to increment of Earth temperature. Our study provide temperature trend of small scope observation unit, the urban area of Palembang City at latitude 2,9° and longtitude 104,7° for 30 years, from 1991-2020. Linear regression analysis shown the temperature increase on skin temperature (TS) and temperature at 2 meter range (T2M) are 0,4°C and 0,46°C, respectively. These variable can become indicator of global warming occurance on small scope of observation unit.Keywords: Global warming, Temperature trend, Linear regression